Full childcare coverage: Higher maternal labour supply and childcare usage? - Pieter Vanleenhove (University of Essex, Institute for Social and Economic Research (ISER), 2013)
According to many studies, childcare is an important input for children's development but it is also used to free up time for parents to work. However, many households are still confronted with availability constraints in childcare. In the recent past, many governments implemented policy reforms in order to increase the coverage rate of childcare. The empirical part of this paper focuses on the Flemish childcare market and analyzes how maternal labour supply and childcare usage is affected by a new Flemish decree which provides full childcare coverage. This paper adopts a modeling framework for analyzing labour supply developed by Aaberge, Colombino and Strøm (1999) and Dagsvik (1994). To account for the possible interaction between labour supply and childcare choices the model also treats childcare type as an endogenous variable. The results of the policy reform analysis show that households switch to formal childcare when confronted with higher childcare availability. Total labour supply also increases but these effects are less pronounced as some households also reduce working hours.
Keywords: C35; H24; J13; J22; D10; 330; Labour supply; Childcare; Microsimulation